Necrotizing Fasciitis and Toxic Shock Syndrome from Clostridium septicum following a Term Cesarean Delivery - B. H. Rimawi; W. Graybill; J. Y. Pierce; M. Kohler; E. A. Eriksson; M. T. Shary; B. Crookes; D. E. Soper (Case Reports in Obstetrics and Gynecology)
Necrotizing fasciitis and toxic shock syndrome are life-threatening conditions that can be seen after any surgical procedure. With only 4 previous published case reports in the obstetrics and gynecology literature of these two conditions occurring secondary to Clostridium septicum, we describe a case of necrotizing fasciitis and toxic shock syndrome occurring after a term cesarean delivery caused by this microorganism, requiring aggressive medical and surgical intervention.